The Role of Social Media in Influencing Body Image and Eating Habits Among Young Adults - Rafael Silva; Lucas Ferreira; Ana Oliveira (International Journal of Health and Social Behavior, 2024)
This study examines the impact of social media on body image perception and eating habits among young adults in Brazil. By analyzing survey responses and social media usage patterns, the research explores how online platforms contribute to body dissatisfaction, unhealthy dieting, and disordered eating behaviors. Findings reveal that frequent exposure to idealized body images and fitness-related content on social media is linked to negative self-perception and a greater likelihood of engaging in restrictive or compensatory eating practices. These results underscore the importance of digital health awareness programs aimed at promoting positive body image and balanced eating habits.